Competing intramolecular N–H...O=C hydrogen bonds and extended intermolecular network in 1-(4-chlorobenzoyl)-3-(2-methyl-4- oxopentan-2-yl) thiourea analyzed by experimental and theoretical methods - Saeed, Aamer (2014)
The synthesis of a novel 1-acyl-thiourea species (C14H17N2O2SCl), has been tailored in such a way that two distinct N–H...O=C intramolecular competing hydrogen bonds are feasible. The X-ray structure analysis as well as the vibrational (FT-IR and FT-Raman) data reveal that the S conformation is preferred, with the C=O and C=S bonds of the acyl-thiourea group pointing in opposite directions. The preference for the intramolecular N–H...O=C hydrogen bond within the –C(O)NHC(S)NH– core is confirmed. The Natural Bond Orbital and the Atom in Molecule approaches demonstrate that a strong hyperconjugative lpO → σ∗(N–H) remote interaction between the acyl and the thioamide N–H groups is responsible for the stabilization of the S conformation. Intermolecular interactions have been characterized in the periodic system electron density and the topological analysis reveals the presence of an extended intermolecular network in the crystal, including a Cl⋯N interaction playing a relevant role in crystal packing.